A Guide for Substitute and Interim Teachers Practical Tools for Success. - Washington, Barbara (Milton : Eye On Education, Incorporated, 2021)
If you're a substitute or interim teacher, or thinking of becoming one, you won't want to miss the techniques and strategies in this user-friendly, easy-to-read book. Author Barbara Washington guides you through every step, including the application process, lesson planning, classroom management, and school safety. Each chapter offers practical examples and current best practices to support you on your way to success. The book also includes essential tools such as reproducible lesson plans, worksheets, graphic organizers, and more. Concise but complete, this is an ideal resource for substitute teacher professional development.
Reproducible Lesson Plans and Worksheets -- Reproducible Graphic Organizers -- 3 Teaching, Learning, and Assessment -- Teaching Strategies -- Learning Principles -- Technology in Education -- Diverse Learners -- Grading -- Testing -- Standardized Assessment -- 4 Classroom Management -- The Importance of Classroom Management -- Getting Class Started -- Maintaining the Learning Environment -- Managing Behavior -- Dismissal Procedures -- 5 School Safety -- The Importance of School Safety -- General Overview -- Closing Thoughts -- Recommended Resources -- Glossary of Terms
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Substitute teaching -- Handbooks, manuals, etc; Substitute teachers -- In-service training; EDUCATION / Classroom Management; BUSINESS & ECONOMICS / Careers / Job Hunting